Isomeric Naphtho‐Fused 7‐Deazapurine Nucleosides and Nucleotides: Synthesis, Biological Activity, Photophysical Properties and Enzymatic Incorporation to Nucleic Acids. Issue 37 (11th May 2018) - Ghosh, Ketaki; Perlíková, Pavla; Havlíček, Vojtěch; Yang, Chao; Pohl, Radek; Tloušťová, Eva; Hodek, Jan; Gurská, Soňa; Džubák, Petr; Hajdúch, Marián; Hocek, Michal
Abstract : Two series of substituted benzo[ g ]‐ or benzo[ e ]pyrimido[4, 5‐ b ]indole (naphtho‐fused 7‐deazapurine) ribonucleosides were synthesized. The heterocyclic nucleobases were obtained by Negishi cross‐coupling reaction of zincated pyrimidines with naphthyl iodides, nucleophilic substitution to tetrazoles/azides and thermal cyclization or photocyclization. Nucleosides were obtained by glycosylation followed by substitution reactions and deprotection. Resulting ribonucleosides were tested for their cytotoxic activity against cancer cell lines and antiviral activities. Some derivatives showed micromolar cytotoxic activities and moderate anti ‐hepatitis C virus activities. Naphtho‐fused 7‐deazapurine 2′‐deoxyribonucleoside triphosphate was successfully incorporated into DNA oligonucleotides by KOD XL DNA polymerase. Fluorescence properties of naphtho‐fused 7‐deazapurine nucleosides and oligonucleotides were also studied. Abstract : Two isomeric series of bulky naphtho‐fused 7‐deazapurine nucleosides were prepared and shown to exert moderate cytostatic and antiviral activity and interesting fluorescent properties. The 2′‐deoxyribonucleoside triphosphates were substrates for KOD XL DNA polymerase.